LTA4H genotype is associated with susceptibility to bacterial meningitis but is not a critical determinant of outcome. - Sarah J Dunstan; Trinh Thi Bich Tram; Guy E Thwaites; Tran Thi Hong Chau; Nguyen Hoan Phu; Tran Tinh Hien; Jeremy J Farrar; Marcel Wolbers; Nguyen Thi Hoang Mai (PLoS ONE, 2015)
Adjunctive dexamethasone saves lives in the treatment of tuberculous meningitis but this response is influenced by the patient's LTA4H genotype. Despite less certain benefit, adjunctive dexamethasone is also frequently used in the treatment of pyogenic bacterial meningitis, but the influence of LTA4H genotype on outcomes has not been previously investigated. We genotyped the LTA4H promoter region SNP (rs17525495) in 390 bacterial meningitis patients and 751 population controls. rs17525495 was associated with susceptibility to bacteriologically confirmed bacterial meningitis (P = 0.01, OR 1.27 95% confidence interval [CI] 1.05-1.54) but did not influence clinical presentation, disease severity or survival following dexamethasone treatment.